2012
DOI: 10.1097/01.ogx.0000418573.67515.1b
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Oocyte Donation and Maternal and Perinatal Outcomes in Women Aged 43 Years or Older

Abstract: Advanced maternal age is a significant risk factor for pregnancy complications. Increasing numbers of women older than 40 years are attempting to conceive. Many of these older women are unable to conceive spontaneously and use assisted reproductive techniques, often with oocyte donation. There are little comparative data on the consequences of in Obstetrical Complications 405

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Nevertheless, we did set forth such likely correlation, that is, the recipient's immunological reaction seemed to be triggered against the presence of unknown genetic matter. Several studies have highlighted an increased rate of pregnancy‐induced hypertension and preeclampsia in patients who underwent in vitro fertilization by oocyte donation versus oocytes of the recipient (OR = 3.3; 95% CI [1.2–8.9]) . We believe that this higher pregnancy‐induced hypertension and preeclampsia can be explained by the recipient's immunological reaction triggered against the presence of unknown genetic matter, that is, allogeneic graft.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, we did set forth such likely correlation, that is, the recipient's immunological reaction seemed to be triggered against the presence of unknown genetic matter. Several studies have highlighted an increased rate of pregnancy‐induced hypertension and preeclampsia in patients who underwent in vitro fertilization by oocyte donation versus oocytes of the recipient (OR = 3.3; 95% CI [1.2–8.9]) . We believe that this higher pregnancy‐induced hypertension and preeclampsia can be explained by the recipient's immunological reaction triggered against the presence of unknown genetic matter, that is, allogeneic graft.…”
Section: Discussionmentioning
confidence: 89%
“…Birthweight reported in six studies showed no significant difference (Figure ) . The risk of preterm delivery was analysed in nine studies, and the fixed‐effect model showed that the risk of preterm birth was significantly higher in DO pregnancy compared with autologous IVF pregnancy [ n / N = 194/1011 (19%) versus n / N = 1078/11 651 (9%), OR 1.34, 95% CI 1.08–1.66, I 2 = 38%; Figure ] . The risk of caesarean section was significantly increased in DO pregnancy [ n / N = 435/690 (88%) versus n / N = 3452/10 283 (33%), OR 2.71, 95% CI 2.23–3.30, I 2 = 43%; Figure ] .…”
Section: Resultsmentioning
confidence: 99%
“…The risk of preterm delivery was analysed in nine studies, and the fixed‐effect model showed that the risk of preterm birth was significantly higher in DO pregnancy compared with autologous IVF pregnancy [ n / N = 194/1011 (19%) versus n / N = 1078/11 651 (9%), OR 1.34, 95% CI 1.08–1.66, I 2 = 38%; Figure ] . The risk of caesarean section was significantly increased in DO pregnancy [ n / N = 435/690 (88%) versus n / N = 3452/10 283 (33%), OR 2.71, 95% CI 2.23–3.30, I 2 = 43%; Figure ] . Neither the increased risk of IUD, analysed in two studies [ n / N = 4/303 (1.3%) versus n / N = 3/346 (0.8%), OR 1.39, 95% CI 0.32–6.15], nor the increased risk of developing gestational diabetes for the mother, analysed in five studies [ n / N = 58/524 (11%) versus n / N = 52/519 (10%), OR 1.25, 95% CI 0.68–2.30], was statistically significant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we have no data on the independent effect of different technologies of assisted reproduction, such as ovum donation. Although many studies have attempted to evaluate obstetric and perinatal complications in women conceiving with different ART, it is unclear whether ART procedures or maternal factors associated with infertility contribute to these adverse outcomes …”
Section: Discussionmentioning
confidence: 99%